Positive peace : reflections on peace education, nonviolence, and social change - Fitz-Gibbon, Andrew L., 1951- (Value inquiry book series, 2010)
This book addresses positive peace. In his introduction, Arun Gandhi, fifth grandson of Mahatma Gandhi, asks, "For generations human beings have strived to attain peace, but with little or no success. Why is peace so illusive?" Twelve philosophers and educators suggest creatively and pragmatically that peace education has a large part of play in meeting the challenge. --Book Jacket.